The Gambia : Seventh Review of the Arrangement Under the Extended Credit Facility, Request for Rephasing of the Eighth Review and Extension of the Arrangement, and Request for Waivers of Nonobservance of Performance Criteria-Staff Report; Informational Annex; Public Information Notice; Press Release on the Executive Board Discussion; and Statement by the Alternate Executive Director for The Gambia. (IMF Staff Country Reports; Country Report ;, 2011)
The Gambian economy performed well in the face of external shocks under the Extended Credit Facility. Executive Directors welcomed the 2011 budget, which focuses mainly on revenue enhancement, limiting government's domestic borrowing, and reduction of poverty. They agreed that IMF engagement has helped in anchoring the macroeconomic policy framework, fiscal adjustment, and signaling the donor community. Directors noted the recommendations of the Ex Post Assessment update and agreed that IMF engagement with The Gambia had a positive impact and granted an extension of the current arrangement.